1993
DOI: 10.1152/ajpregu.1993.265.4.r792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anesthesia on cardiac and renal sympathetic nerve activities and plasma catecholamines

Abstract: The effects of pentobarbital and chloralose on cardiac sympathetic nerve activity (CSNA), renal sympathetic nerve activity (RSNA), arterial pressure (AP), and heart rate (HR) were examined using conscious cats. Arterial blood was sampled intermittently to measure plasma epinephrine. Pentobarbital (25-30 mg/kg iv) decreased CSNA, RSNA, AP, and HR. The reduction of CSNA (71 +/- 7%) was larger and lasted longer than that of RSNA (33 +/- 12%). Chloralose (40-50 mg/kg iv) decreased CSNA 66 +/- 9% and HR, increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 0 publications
4
44
0
Order By: Relevance
“…The lack of the effect of kynurenate appeared to be due to the pentobarbital sodium anesthesia severely compromising the baroreflex gain, which is likely to limit the ability of the premotor neurons to be further inhibited. The strong inhibiting action of barbiturate anesthesia on the baroreflex gain has also been reported previously (18,31). Although other commonly used anesthetics, such as urethane and chloralose, generally inhibit baroreflexes to a lesser extent (19,37), chloralose-urethane still reduces the RSNA baroreflex gain to ϳ60% of the value in conscious rabbits (10,11).…”
Section: Discussionsupporting
confidence: 66%
“…The lack of the effect of kynurenate appeared to be due to the pentobarbital sodium anesthesia severely compromising the baroreflex gain, which is likely to limit the ability of the premotor neurons to be further inhibited. The strong inhibiting action of barbiturate anesthesia on the baroreflex gain has also been reported previously (18,31). Although other commonly used anesthetics, such as urethane and chloralose, generally inhibit baroreflexes to a lesser extent (19,37), chloralose-urethane still reduces the RSNA baroreflex gain to ϳ60% of the value in conscious rabbits (10,11).…”
Section: Discussionsupporting
confidence: 66%
“…The nerve discharges recorded from the feline inferior cardiac nerve, therefore, are considered to originate from sympathetic postganglionic efferent fibers. We found that the cardiac sympathetic nerve is tonically active in the conscious state, but it is very susceptible to anesthesia (17); its firing rate in mass discharge is relatively high (54 Ϯ 12 impulses/s). Obviously this result indicates an existence of basal cardiac sympathetic outflow in the resting condition of conscious cats.…”
Section: Discussionmentioning
confidence: 87%
“…From our previous studies (17,22), the arterial baroreflex sensitivity of CSNA is 1.4-2.3%/ mmHg during resting in conscious cats. It has been considered that the sensitivity of the arterial barore-…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…injected. After catecholamines were purified from plasma, a catecholamine assay was performed by reversed-phase high-pressure liquid chromatography with electrochemical detection according to our previous studies [7][8][9].…”
Section: Methodsmentioning
confidence: 99%